Enhancing Learning Management Skills Of Prospective Mathematics Teachers Through A Project-Based Learning Model Integrated With STEAM - Fauziah Fauziah; Nuramaliyah Ramadhany; Herman Alimuddin; Nur Wahidin Ashari (Universitas Wiralodra, 2025)
This study aims to improve the learning management skills of prospective mathematics teachers through the implementation of Project-Based Learning (PjBL) integrated with STEAM (Science, Technology, Engineering, Art, and Mathematics). The research employed a quantitative approach with a quasi-experimental design, specifically a pretest-posttest non-equivalent control group design. Two groups of students participated: the experimental group using the PjBL-STEAM model and the control group following conventional learning. The research instruments included a learning management competency test, a student perception questionnaire, and PjBL-STEAM-based learning materials. Data were analyzed using descriptive and inferential statistics (t-test and effect size) to evaluate the effectiveness of the model and examine students’ perceptions of its implementation. The results revealed a significant improvement in the learning management skills of students in the experimental group compared to the control group. The PjBL-STEAM model effectively enhanced students’ abilities in planning, implementation, evaluation, and reflection & improvement, while also promoting active engagement, creativity, and self-confidence. These findings suggest that integrating PjBL with STEAM can be an effective strategy to strengthen the pedagogical competencies of prospective mathematics teachers, preparing them to meet the demands of 21st-century education.